Implementation of Numbered Heads Together (NHT) Learning Devices with Quiz Kahoot to Improve Student Learning Outcomes and Collaboration Skills in Reproduction System Materials - Rahayuningtiyas, Astri; Utami, Nur Rahayu (Journal of Biology Education, 2022)
This study aims to analyze student learning outcomes and collaboration skills by applying the Numbered Heads Together (NHT) learning tool model with Quiz Kahoot on the reproductive system material. This type of research is the Pre-Experimental Design with the type of One-Shot Case Study. The sample used was 15 students from class XI MIPA 1 with purposive sampling technique. Students' cognitive learning outcomes were analyzed descriptively quantitatively with the N-gain test and t-test or the difference between the two means. The results of the N-gain test for 15 students of class XI MIPA 1 were 0.4 with moderate criteria. The results of the t-test analysis or the difference between the two mean values ​​obtained sig. 0.002 <0.05, then Ha is accepted and Ho is rejected, so there is a significant difference between pretest and posttest. In addition, there is also an increase in student collaboration obtained from the data from the observation and trial stages. This is supported by the results of student responses related to the application of the Numbered Heads Together (NHT) learning tool model with Quiz Kahoot, which obtained an average student score of 84.17 with very good criteria. Based on the results of the study, it can be concluded that the Numbered Heads Together (NHT) learning device with Quiz Kahoot to improve student learning outcomes and collaboration skills is good for use in SMA PGRI 02 Kayen Pati.